Vacuum polarization alters the spectra of accreting X-ray pulsars - Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Dauser, Thomas; Wilms, Jörn (Astronomy & Astrophysics, 2023)
It is a common belief that for magnetic fields typical of accreting neutron stars in high-mass X-ray binaries vacuum polarization only affects the propagation of polarized emission in the neutron star magnetosphere. We show that vacuum resonances can significantly alter the emission from the poles of accreting neutron stars. The effect is similar to vacuum polarization in the atmospheres of isolated neutron stars and can result in suppression of the continuum and the cyclotron lines. It is enhanced by magnetic Comptonization in the hot plasma and proximity to the electron cyclotron resonance. We present several models to illustrate the vacuum polarization effect for various optically thick media and discuss how the choice of polarization modes affects the properties of the emergent radiation by simulating polarized energy- and angle-dependent radiative transfer. Polarization effects, including vacuum polarization, crucially alter the emission properties. Together with strongly angle- and energy-dependent magnetic Comptonization, they result in a complex spectral shape, which can be described by dips and humps on top of a power-law-like continuum with high-energy cutoff. These effects provide a possible explanation for the common necessity of additional broad Gaussian components and two-component Comptonization models that are used to describe spectra of accreting X-ray pulsars. We also demonstrate the character of depolarization introduced by the radiation fielda's propagation inside the inhomogeneous emission region.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Magnetic fields; Methods: numerical; Polarization; Radiative transfer; Stars: neutron; X-rays: binaries